Reconnaissance Cenozoic volcanic geology of the Little Goose Creek area, northeastern Elko County, NV with an emphasis on the Jarbidge Rhyolite - Ingalls, Andrew (Kansas State University, 2014)
The Little Goose Creek area is located in Elko County, Nevada just south of the central Snake River Plain and in the northeastern Great Basin. During the Miocene, northeastern Nevada was characterized by volcanism as well as prevalent extension and basin development, including widespread occurrences of porphyritic quartz-phyric silicic lavas and domes (e.g., the Jarbidge Rhyolite), ash-flow tuffs, and basaltic volcanism. Recent workers (e.g., Colgan and Henry, 2010) have provided new constraints on the timing of extension in the northern Great Basin (U.S.A.) and indicate that much of it occurred in the mid-Miocene. Other recent work has provided new temporal and petrologic constraints on 16.1 to 15.0 Ma Jarbidge Rhyolite volcanism in the northern Great Basin west of our study area, and suggest that it is intimately linked (spatially and temporally) with the aforementioned extension. This study aims to: [1] understand the spatiotemporal link between the volcanism in the northeastern Nevada study area and potentially correlative volcanism regionally (e.g., Jarbidge Rhyolite and explosive deposits associated with the <13 Ma Bruneau-Jarbidge or Twin Falls eruptive centers); [2] determine if the sampled Jarbidge Rhyolite lavas are chemically similar to those in and around Jarbidge, Nevada. In the Goose Creek area, we report a new laser [superscript]40Ar/[superscript]39Ar age for sanidine of 13.6 ± 0.03 Ma for a crystal-poor rhyolite lava (Rock Springs Rhyolite) and a Jarbidge Rhyolite lava (13.827±0.021 Ma) as well as an age on Jarbidge Rhyolite in Wells, NV (15.249±0.040 Ma) and West Wendover, NV (13.686±0.034 Ma). These lava samples, as well as sampled ash-flow tuffs from the Goose Creek region, plot within the A-type field on discrimination diagrams. The ash-flow tuffs are younger than the Rock Springs Rhyolite based on stratigraphic relationships and are sourced from both the Twin Falls eruptive center as well as the Bruneau Jarbidge eruptive center of the central Snake River Plain based on geochemical analysis. Also, a sequence of basaltic lavas crop out in the Goose Creek drainage; these basalts have ~43 wt.% silica and are chemically similar to <8 Ma olivine tholeiite basalts that crop out to the north, along the southwestern side of the Cassia Mountains, Idaho. These results, field relationships, and prior geological mapping suggest that the lavas and ash-flow tuffs erupted into active extensional basins.
Keywords: Elko County; Jarbidge Rhyolite; Cenozoic; Nevada; Volcanic Geology; Geology (0372)